Applied Behavior Analysis for the Treatment of Autism: A Systematic Review of Assistive Technologies - Fabio Junior Alves; Emerson Assis De Carvalho; Juliana Aguilar; Lucelmo Lacerda De Brito; Guilherme Sousa Bastos (IEEE Access, 2020)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder that may lead to significant impairment in social communication, repetitive patterns of behavior, and possible fixed and restricted interests. Applied Behavior Analysis (ABA) is a well-supported and evidence-based treatment for the delays attributed to ASD. Assistive technologies, such as gamification, software apps, computer-based training (Web), and robotics; provide a standardized method of implementing ABA techniques. This review provides a synthesis of the main characteristics of these technologies. The assessed proposals focused on technologies such as Distributed Systems, Image Processing, Gamification, and Robotics. The primary objectives of these tools sought to improve social behavior, attention, communication, and reading skills. Some common limitations found in the literature was a failure to accurately define their target audience, and a failure to comply with the dimensions of ABA as defined by Baer, Wolf, and Risley in 1968.